Pengembangan LKPD dengan Bantuan Artificial Intelligence (AI) Materi Penyajian Data untuk Penguatan Kemampuan Numerasi - Sopani, Ahmad; Hartatiana, Hartatiana; Atika, Zahra; Putri, Agustiany Dumeva; Agustiani, Riza (MATHEdunesa, 2024)
This study aims to determine the validity and practicality of student worksheets with the help of Artificial Intelligence (AI) to strengthen numeracy skills in algebraic operation material. This type of research is preliminary and formative evaluation stage research. At the preliminary stage, product preparation and design have been carried out. Furthermore, the formative evaluation stage involves expert review, one-to-one, small group, and field test stages. The material used was data presentation, questions based on numeracy literacy, and some related to numeracy literacy indicators. The data collection techniques used were questionnaires and interviews. Questionnaires consisting of validity and practicality questionnaires. Validity data was obtained from comments and suggestions from experts. Practicality data were obtained through questionnaires and interviews that were analyzed qualitatively. The potential effect can be seen from the calculation of the evaluation results. The research subjects used were grade VII students at SMP Negeri 31 Palembang. The results showed that student worksheets with the help of AI were declared valid at the expert review stage and declared practical from the results of practical questionnaires and interviews in the one-to-one, small group.